A predictive study about Organizational Support and Psychological Capital at work regarding emotional disorder during Covid-19 isolation period (Research, Society and Development, 2022)
Psychological Capital and Organizational Support are fields that propose a rescue of the subject's importance, considering the implication for the work environment, motivated actions, and the psychic power that leads a human being to achieve better organizational performance. Thus, the goal of this chapter is to verify if there is a connection between organizational support, positive psychological capital at work, and emotional disorder in workers from public and private companies, during the period of isolation caused by the pandemic of Covid-19. It is a field research, and also a quantitative and correlational one. To collect data, we used: a questionnaire of work and sociodemographic criteria, the Positive Psychological Capital Scale at work (PPCS), the Organizational Support Scale (OSS), and the Depression Anxiety and Stress Scale (DASS-21). 201 workers took part in this research. Through the use of SPSSWIN (version 24.0), a data analytics software, it was possible to produce statical analysis, from which we observe an intern consistency on the scales used and a predictive, hierarchical, positive power of the organizational support connected to the positive psychological capital, impacting negatively on the ordinary emotional disorder.